Masjid Aziziyah dalam Lintasan Sejarah Kesultanan Musa dan Dinamika Kehidupan Keagamaan Masyarakat Melayu - Shakira Rahmadani Putri; Riski Ananda Siregar; Suci Shalwa Fauzi; Ahmad Dwi Pramanda; Sugeng Wanto (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
This study aims to analyze the urgency of listing business locations on digital platforms such as Google Maps, with a case study on the small and medium enterprise (SME) producing tempeh “Nek Timbli” in Bandar Malela Village. The push for economic digitalization has become one of the key factors in increasing the competitiveness of SMEs in the era of Industry 4.0. The availability of online business location information is expected to improve SME visibility, expand consumer reach, and support local economic growth. This research employs a qualitative method with a case study approach, involving direct interviews with the business owner, field observations, and literature analysis on SME digitalization. The findings reveal that listing the business location on Google Maps has a positive impact by increasing customer visits, facilitating access to information, and strengthening business image. This study highlights the importance of digital technology adoption by SMEs to face increasingly intense market competition. Therefore, digitalizing business location becomes an effective strategy to accelerate rural economic transformation.